Positioning of nursing professionals before the law of dignified death and in patients with irreversible cessation of encephalic functions - Guzmán, Camila (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Dignified death constitutes a relevant and controversial issue within health care, especially in the management of patients with irreversible cessation of encephalic functions. This concept is linked to the right to health, which includes the possibility of ending life when it is not adequate and of rejecting treatments that artificially prolong life. In Argentina, National Law No. 26742, enacted in 2012, regulates the rights of patients with irreversible conditions and promotes comprehensive health care based on respect for human dignity. Nursing professionals, being in constant contact with patients, play a crucial role in the implementation of this legislation, ensuring the quality of care and respecting bioethical principles.Methods: A normative and scientific literature review was carried out on National Law No. 26742 and its application in the care of patients with irreversible cessation of encephalic functions. The roles of the medical teams were analyzed, with special emphasis on the nursing staff, in order to identify their contribution in the fulfillment of the rights established by the legislation and in the provision of care aimed at guaranteeing a dignified death.Results: The review showed that health professionals, particularly nurses, have a significant responsibility in the implementation of care that ensures respect for the dignity of the terminally ill patient. However, deficiencies were detected in the ethical and technical training of personnel with respect to current legislation and applicable bioethical principles. In patients with irreversible cessation of encephalic functions, compliance with regulations was related to a better perception of quality in health care and greater satisfaction of the patient's relatives.Conclusions: Dignified death is a fundamental right that should be guaranteed through comprehensive and humanized care, especially in patients with irreversible conditions. National Law No. 26742 provides a clear regulatory framework, but its implementation requires healthcare personnel trained in both ethical aspects and specific care. Nursing professionals should play a key role in the application of these principles, ensuring respect for patient dignity and promoting quality care that complies with bioethical standards. Continuous training and awareness of issues related to dignified death are essential to improve health care in this area.